ANALISA PENGUKURAN BEBAN KERJA MENTAL KARYAWAN PADA BAGIAN MAINTENANCE PT. XYZ - Nicholas Tjang; Sadiq Ardo Wibowo (JURNAL LOGISTICA, 2022)
PT. XYZ is a smartphone manufacturer that does mass production. Technicians at this company must optimize their performance so that the machines that work don't have problems and don't hinder production workflow. In this study, the measurement of the workload of technicians at PT. XYZ to see how the mental load of technicians, especially technicians in the production section, uses the nasa-tlx method. Measurements were made of 25 technicians working on the smartphone production process at pt.xyz. The results of measuring mental workload using the NASA-TLX method showed that the 25 technicians who were respondents had mental workload in the high category. The factor that most influences the workload at PT. XYZ is a factor of mental demands (md), physical demands (pd), and self-performance (pf).